The Missions of Autonomous Public Libraries from the Point of View of Quebec Municipal Elected Officials: An Analysis of Discourses - Gazo, Dominique (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The principal objective of this thesis is to understand, via the discourses, the point of view of the Québécois municipal elected officials on the missions of the autonomous public libraries as well as the distance between these discourses and the practices of the libraries at the local level. L'objectif principal de cette thèse est de comprendre, grâce aux discours, le point de vue des élus municipaux du Québec quant aux missions des bibliothèques publiques autonomes ainsi que l'écart entre ces discours et les pratiques des bibliothèques à l'échelle locale.